5-year Effects of Potassium Fertilization Levels on Nutrition Balance and Yield in the Maize/Soybean Succession. Issue 16 (8th September 2022) - Bossolani, João William; Meneghette, Hugo Henrique Andrade; Sanches, Izabela Rodrigues; Dos Santos, Fabiana Lopes; Parra, Lucas Fenelon; Lazarini, Edson
ABSTRACT: Potassium (K)-based fertilizers are highly demanded in crop systems, as they are one of the elements most required by plants. Due to the high rates of K-fertilizers applied consecutively in agriculture and the doubts generated as to their permanence in soil and possible negative effects in a subsequent crop, there is a need for long-term studies that evaluate the residual effect of applications of these fertilizers on nutritional status and yield crops that make up the crop system. This study aimed to verify the effect of K-fertilizer doses applied in topdressing in maize on crop nutrition and yield, as well as soybean in succession. Nine doses of K2 O (0, 15, 30, 45, 60, 75, 90, 120 and 150 kg ha −1 ) were applied to maize. The nutritional status and yield components were evaluated. Our results reveal the beneficial effect of applications, between 70 and 80 kg K2 O ha −1 on maize nutrition and yield, as well as on soybean in succession. Consecutive K2 O application in doses over 90 kg ha −1, strongly reduce the levels of leaf Ca and Mg in maize and soybean leaves and their respective grain yields.